2016
DOI: 10.1177/0269881116647504
|View full text |Cite
|
Sign up to set email alerts
|

Mineralocorticoid receptor haplotype moderates the effects of oral contraceptives and menstrual cycle on emotional information processing

Abstract: MR-haplotype 1/3 carriers may be more sensitive to the influence of their female hormonal status. MR-haplotype 2 carriers showed more risky decision-making. As this may reflect optimistic expectations, this finding may support previous observations in female carriers of MR-haplotype 2 in a naturalistic cohort study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 60 publications
0
17
0
Order By: Relevance
“…While investigating the effects of a corticosteroid (fludrocortisone) in a clinical trial, Hamstra et al ( 2014 ) found that the use of oral contraceptives by women in their sample was associated with lower accuracy in the recognition of sadness, anger, and disgust. Four other cross-sectional studies reached the same results for the same emotions when comparing users of oral contraceptives and women in their natural menstrual cycle (Maner and Miller, 2014 ; Hamstra et al, 2015 , 2016 , 2017 ), although another investigation with the same methodological design did not support these findings (Radke and Derntl, 2016 ). Hamstra et al ( 2017 ) also described impaired recognition of facial happiness in association with the use of oral contraceptives.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…While investigating the effects of a corticosteroid (fludrocortisone) in a clinical trial, Hamstra et al ( 2014 ) found that the use of oral contraceptives by women in their sample was associated with lower accuracy in the recognition of sadness, anger, and disgust. Four other cross-sectional studies reached the same results for the same emotions when comparing users of oral contraceptives and women in their natural menstrual cycle (Maner and Miller, 2014 ; Hamstra et al, 2015 , 2016 , 2017 ), although another investigation with the same methodological design did not support these findings (Radke and Derntl, 2016 ). Hamstra et al ( 2017 ) also described impaired recognition of facial happiness in association with the use of oral contraceptives.…”
Section: Discussionmentioning
confidence: 75%
“…Group 2—Oral contraceptives: studies with women using oral contraceptives, taking women at different phases of the natural menstrual cycle as a reference, with both observational ( n = 5) (Maner and Miller, 2014 ; Hamstra et al, 2015 , 2016 , 2017 ; Radke and Derntl, 2016 ) and experimental ( n = 2) (Gingnell et al, 2013 ; Hamstra et al, 2014 ) designs.…”
Section: Resultsmentioning
confidence: 99%
“…Hap 2 carriers appeared less sensitive to variations in female hormone exposure during the reproductive cycle and to the depressinogenic side effects of oral contraceptives. The MR genotype moderates the influence of oestrogen and progesterone on emotional information processing (Hamstra et al 2015(Hamstra et al , 2016(Hamstra et al , 2017. The MR gene variants were found to sex-dependently moderate the effect of early life trauma on vulnerability to depression in a population-based cohort (n = 665) and an independent clinical cohort from the Netherlands Study of Depression and Anxiety (n = 1639).…”
Section: Common and Functional Mr Haplotypes Might Relate To The Extementioning
confidence: 99%
“…Thus, the MR can operate as a key regulator in a mechanism underlying resilience to stress. Such a crucial role of the brain MR in human resilience is underscored by variations in MR genotype, which were found to predict stress coping style and protection to depression, and by epigenetic modifications of the MR induced by (early) adversity (see Joëls et al 2012, Bigio et al 2016, de Kloet et al 2016.…”
Section: Perspectivesmentioning
confidence: 99%
“…In terms of differences in sample, there may be variables that were either not measured or not of specific interest in the current study that interact with hormonal status and/or brooding rumination in order to produce the anticipated outcome. For example, hormonal contraceptive using women with mineralocorticoid receptor haplotype two have been found to be less affectively impacted by aversive stimuli when compared to women with haplotype one or three (Hamstra et al, 2016). Combined hormonal contraceptives additionally vary in the generation of progestin used in formulation, with older generations having more androgenic effects than more recent generations.…”
Section: Discussionmentioning
confidence: 99%